2019
DOI: 10.1371/journal.pone.0222961
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia in the early stages of type 1 diabetes accelerates gastric emptying through increased networks of interstitial cells of Cajal

Abstract: Gastric emptying (GE) can be either delayed or accelerated in diabetes mellitus (DM). However, most research has focused on delayed GE mediated by a chronic hyperglycemic condition in DM. As such, the function of GE in the early stages of DM is not well understood. Interstitial cells of Cajal (ICC) are pacemaker cells in the gastrointestinal tract. In the present study, we investigated changes in GE and ICC networks in the early stages of DM using a streptozotocin-induced type 1 diabetic mouse model. The chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Previous studies suggested that loss of ICC-MP is associated with many GI motility disorders such as diabetic gastroparesis, ulcerative colitis, and ileus ( Choi et al, 2008 ; Kaji et al, 2018 ; Lu et al, 2019 ). In addition, recent reports have shown that increased ICC-MP are associated with rapid gastric emptying, which is often observed in diabetes ( Hayashi et al, 2017 ; Kishi et al, 2019 ). The present study conclusively showed that GI transit was strongly influenced by ICC-MP networks in vivo .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous studies suggested that loss of ICC-MP is associated with many GI motility disorders such as diabetic gastroparesis, ulcerative colitis, and ileus ( Choi et al, 2008 ; Kaji et al, 2018 ; Lu et al, 2019 ). In addition, recent reports have shown that increased ICC-MP are associated with rapid gastric emptying, which is often observed in diabetes ( Hayashi et al, 2017 ; Kishi et al, 2019 ). The present study conclusively showed that GI transit was strongly influenced by ICC-MP networks in vivo .…”
Section: Discussionmentioning
confidence: 98%
“…Gastric emptying in mice was evaluated using the 13 C-octanoic acid breath test according to previous studies ( Creedon et al, 2013 ; Kishi et al, 2019 ). In preparation for this test, mice were fasted for 18 h. The test meal was 200 mg of a solid meal consisting of heated egg yolk and 0.2 μL 13 C-octanoic acid (Cambridge Isotope Laboratories, Inc., MA, United States).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wide glycemic fluctuations and impact on quality of life are also noticed in DGP patients [3,4]. e possible pathogenesis of DGP includes multiple factors, such as vagus neuropathy, abnormal myenteric neurotransmission, damage of inhibitory neuronal function, and the impaired function of smooth muscle cells and interstitial Cajal cells (ICCs) [5][6][7]. e suggested treatment for DGP depends on the severity.…”
Section: Introductionmentioning
confidence: 99%